Climate-smart management of soil water storage: statewide analysis of California perennial crops. (9th April 2019) - Devine, Scott; O'Geen, Anthony (Toby)
Abstract: The FAO-56 dual crop coefficient model was used to simulate site-specific irrigation management to quantify the green water resource (rainfall stored in soil) in five California perennial crops (alfalfa, almonds, grapes, pistachios, and walnuts), considering local soil water holding capacity and climate data from 2003 to 2018. We tested different rooting depths and irrigation management thresholds (allowable depletion) across 1.46 million hectares of cropland to determine how the size of the soil water reservoir affects green water utilization and, consequently, blue water demand (irrigation). The 13-year cumulative green water utilization ranged from 17 to 36 million km 3 out of a 57 km 3 rainfall input and 162–263 km 3 cumulative blue water demand. For a deep scenario (2 m rooting; 50% allowable depletion), green water met 12% of cumulative crop water demand. However, green water use was not uniform: 20% of the landscape met over 20% of its annual crop water demand. Deeper rooting or greater allowable depletion reduced blue water demand more than the increase in green water utilization, due to less frequent irrigations, which reduced soil evaporative loss. Compared to a 'business-as-usual' shallow irrigation management scenario (0.5 m rooting; 30% allowable depletion), a moderate scenario (1.0 m rooting; 50% allowable depletion) saved 30 km 3 blue water evaporation and increased green water use by 7 km 3 through 13 years. Such savings would fill California's largest reservoir, Shasta Lake, 6.6 times. This study demonstrates an opportunity for climate-smart management of soil water storage, by delayed spring irrigation, applying deeper irrigations less often, and ending fall irrigation early.